Method for the Determination of Vitamin K Homologues in Human Plasma Using High-Performance Liquid Chromatography-Tandem Mass Spectrometry - Suhara, Yoshitomo; Kamao, Maya; Tsugawa, Naoko; Okano, Toshio (Analytical chemistry (Washington), 2005)
We report here the development of a precise and sensitive method for the determination of vitamin K homologues including phylloquinone (PK), menaquinone-4 (MK-4), and menaquinone-7 (MK-7) in human plasma using HPLC-tandem mass-mass spectrometry with atmospheric pressure chemical ionization (LC-APCI-MS/MS). The method involves the use of stable isotope 18O-labeled internal standard compounds, which were synthesized in our laboratory, and the selection of a precursor and product ion with a MS/MS multiple reaction monitoring method. The average intraassay and interassay variation values for PK, MK-4, and MK-7 were <10%. Average spiked recoveries from authentic compounds added to normal human plasma samples for PK, MK-4, and MK-7 were 98−102%. Mean plasma concentrations of PK, MK-4, and MK-7 from healthy subjects (n = 20) were 1.22 ± 0.57, 0.39 ± 0.46, and 6.37 ± 7.45 ng/mL, respectively. We conclude that this novel LC-APCI-MS/MS method should be useful for the evaluation of vitamin K status in postmenopausal women and elderly subjects and provides useful information for the treatment and prevention of osteoporosis with vitamin K.